Detection Extended Spectrum β-Lactamase (ESBL) and Carbapenemase encoding Klebsiella pneumoniae isolates from hospital effluent wastewater and hospital adjacent community tap water in Dhaka metropolitan city - Siddique, Sifat Sarwa; Noor, Shah (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Microbiology, 2023.